Piranti Kohesi Gramatikal Dan Leksikal Pada Wacana Rubrik "Selebritas" Dalam Majalah FeminaSebagai Bahan Ajar Menulis Teks Narasi - Prima Septianingrum, Nila; Dra.AtiqaSabardila,, Dra.AtiqaSabardila,M.Hum (2016)
The purpose of this study are (1) describes the use of grammatical cohesion devices in the rubric "Selebritas" in the Femina magazine, (2) describes the use of lexical cohesion devices in the rubric "Selebritas" in the Femina magazine, and (3) implement the use of grammatical and lexical cohesion devices in rubric "Selebritas" in Femina magazine as one of the teaching material to write narrative texts. Data collection techniques were used that refer to the log and documentation techniques. Data were analyzed an frontier method, agih, and read many. The basic techniques on a frontier method is aggregated referential power. Basic techniques on agih method is for an element of direct and advanced techniques is insertion technique. The first research purpose is achieved by sorting referential power, insertion method, and read many. The second research purpose is achieved with sorting referential power and many reading techniques. The results of this study were (1) grammatical cohesion devices analyzed in this study consisted of 10 reference, 6 conjunction, 3 substitution, and 3 ellipsis. Counterfeit reference cohesion divided into 7 reference persona, 2 demonstrative reference and 1 comparative reference. Reference persona is divided into 1 pronoun first person singular, 1 pronoun first person plural, 4 pronouns third person singular, and 1 pronouns third person plural, (2) lexical cohesion devices analyzed in this study consisted of 7 equivalence, 2 hyponymy, 2 antonym, 2 repetition, 1 synonymy and 1 collocation and (3) the results of this research are used as teaching material in high school students of class VII in accordance with Curriculum 2013. These teaching materials can be applied to core competencies 4 and basic competence 4.5.1 which students were asked to compile a narrative text. Keywords: grammatical cohesion devices, lexical cohesion devices, teaching materials, narrative texts.